SAPA Paradigma Baru Sistem Akuntansi Sektor Publik dalam Pelaksanaan Otonomi Daerah - Lilis Setiartiti (Universitas Muhammadiyah Yogyakarta, Indonesia, 2002)
With the enactment of the law on regional autonomy and its implementing regulations, has led to changes in many aspects of local government birokrase environment. SAPA is a new paradigm scores within the public accounting system in anticipation of the implementation of regional autonomy. SAPA give a new alternative in local government accounting system previously used single entry. SAPA implementation is expected to improve the performance and direction of pemangunan area. By SAPA performance reports will be more comprehensive local, regional wealth will always be detected, accounting more secure, can be used as a reference for more accurate budgeting. Besides, the SAPA accounting information will be more accurate for local governments to make decisions because of the financial statements which are presented not only with cash flow considerations.